Gene silencing: a therapeutic approach to combat influenza virus infections. (January 2015) - Khanna, Madhu; Saxena, Latika; Rajput, Roopali; Kumar, Binod; Prasad, Rajendra
ABSTRACT : Selective gene silencing technologies such as RNA interference (RNAi) and nucleic acid enzymes have shown therapeutic potential for treating viral infections. Influenza virus is one of the major public health concerns around the world and its management is challenging due to a rapid increase in antiviral resistance. Influenza vaccine also has its limitations due to the emergence of new strains that may escape the immunity developed by the previous year's vaccine. Antiviral drugs are the primary mode of prevention and control against a pandemic and there is an urgency to develop novel antiviral strategies against influenza virus. In this review, we discuss the potential utility of several gene silencing mechanisms and their prophylactic and therapeutic potential against the influenza virus.